HUBUNGAN PERSEPSI KERENTANAN DAN PERSEPSI ANCAMAN DENGAN PERAN PMO DALAM PEMBERIAN OBAT TB PADA ANAK TERHADAP PENCEGAHAN KEJADIAN DROP OUT - Intannia Islami Dewi; Priyadi Nugraha Prabamurti; Ratih Indraswari (Jurnal Kesehatan Masyarakat (Undip), 2019)
Tuberculosis (TB) is a disease caused by Mycobacterium tuberculosis. Cases of TB in children can cause various problems such as disability, memory loss, stunting and causing death. PMO is a person who plays a role in the supervision of taking medication in patients with TB. PMO also acts as a motivator and encouragement for TB sufferers to continue taking the medicine. The role of the PMO has a big influence on the prevention of Drop Out. The purpose of this study was to analyze the relationship between perception of vulnerability and perceived threat to the role of PMO in the delivery of TB drugs to children against the prevention of Drop Out. This research is a quantitative study with cross sectional research design. The sample in this study is the PMO of TB children in the city of Semarang with a total of 113 people. Data collection was conducted by interview using a questionnaire. Data analysis was performed using univariate and bivariate analysis. The results of this study note that PMO which has a good role in the administration of TB drugs is 70.8% and those that play an unfavorable role is 29.2%. Bivariate test results show there is a relationship between perception of vulnerability (p-value=0.034) and threat perception (p-value=0.035) with the role of PMO in giving TB drugs to children against the prevention of Drop Out. PMO is expected to have a high perception of vulnerability and threat perception with the aim that PMO can take action to prevent and change behavior so that children who are supervised taking medication can avoid dropout. In addition, PMO is expected to increase its role in supervising TB patients during the treatment period. PMO is expected to have a high perception of vulnerability and threat perception with the aim that PMO can take action to prevent and change behavior so that children who are supervised taking medication can avoid dropout. In addition, PMO is expected to increase its role in supervising TB patients during the treatment period.